The monkey king 3 [videorecording (DVD)] - Guo, Fucheng, 1965-; Feng, Shaofeng, 1978-; Zhao, Zanilia (Well Go USA Entertainment, 2018)
The third installment of the blockbuster fantasy series sees the return of the Monkey King in his most action-packed adventure yet, as the travelers on their journey to the West are imprisoned by the Queen of an all-female kingdom and threatened by the wrathful River God.